CEO Ideational Facilitation Leadership and Team Creativity: The Mediating Role of Knowledge Sharing. (25th January 2014) - Carmeli, Abraham; Paulus, Paul B.
Abstract The development of new ventures is often based on collective creative efforts. We conceptualize team creativity as a process of looking for and exploring new solutions and examine whether and how CEO leadership fosters creativity in top management teams (TMT). Data collected from senior executive teams indicate that CEO ideational facilitation leadership is positively related to team knowledge sharing, which in turn results in enhanced team exploratory behaviors. These findings bear important theoretical implications for ways in which leaders can enhance creativity in teams and augment the entrepreneurial direction of executive teams.